Supporting and Inhibiting Factors In The Application of The Jigsaw Method In Class V Science Subjects In Elementary School - Susanto, Hendi; Sulistyaningrum, Heny (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2024)
This research describes the supporting and inhibiting factors in implementing the Jigsaw method in science learning for class V elementary schools. The type of research used is a case study with a descriptive qualitative approach. Data collection techniques are interviews, observation and documentation. Miles and Huberman model data analysis techniques which include data reduction, data presentation, and data verification. The results of the research show that the supporting factors are the fulfillment of school facilities and infrastructure, as well as the active role of the school, both by teachers and school principals through programs that are able to increase teacher competence in relation to learning at school and the inhibiting factor is that the jigsaw method requires a long time. old and smart students tend not to want to be put together. The application of the jigsaw method in grade V elementary school science learning begins with the preparation of learning tools such as lesson plans. The teacher carries out the implementation process in learning, including initial or opening activities, core activities and final activities. The initial activities were carried out by the teacher by providing motivation and apperception. In the core activity, the teacher implements the Jigsaw method through the steps that have been prepared. In the final activity, the teacher provides a conclusion. The evaluation process is carried out through written tests. The results show effectiveness in the learning process and are able to improve learning outcomes for student.